Enhancing Young Learners’ Speaking Skills through Information Gap Activities - Khamraeva Gulchehra Ibrakhimovna (International Journal on Integrated Education, 2022)
This article highlights the role of information gap activities in developing young learners’ speaking skills. We know implementation of different information gap activities in teaching improves not only young learners’ language skills, but also their critical thinking skills, as well as their communicative competences. Moreover, these activities give motivation to use the language in real situation and help to develop pair work and group work skills.